2005
DOI: 10.1002/mabi.200500018
|View full text |Cite
|
Sign up to set email alerts
|

Folate Receptor‐Mediated Gene Delivery Using Folate‐Poly(ethylene glycol)‐Poly(L‐lysine) Conjugate

Abstract: For efficient receptor-mediated gene transfection, a new and simple formulation method based on using PEI and FOLPEGPLL conjugate was presented. Luciferase plasmid DNA and PEI were complexed to form slightly positive-charged nanoparticles, onto which FOL-PEG-PLL conjugate was surface coated. With increasing the coating amount of FOL-PEG-PLL conjugate, the FOL-PEG-PLL/PEI/DNA complexes exhibited increased surface zeta-potential values with concomitantly increased diameters, indicating that the PLL part was phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 39 publications
3
36
0
Order By: Relevance
“…Tf receptors are overexpressed in rapidly dividing cells due to the increased cellular need for iron. The folate receptor is another example of receptors overexpressed in tumor cells, and it can be used for tumor targeting (Lee and Huang, 1996;Cho et al, 2005). Although receptor-mediated endocytosis is a promising approach for drug tar-UPTAKE PATHWAYS IN NONVIRAL GENE DELIVERY geting, most of the currently used ligands are internalized by clathrin-mediated endocytosis, and the poor intracellular trafficking associated with this significantly limits the transfection activities of the systems.…”
mentioning
confidence: 99%
“…Tf receptors are overexpressed in rapidly dividing cells due to the increased cellular need for iron. The folate receptor is another example of receptors overexpressed in tumor cells, and it can be used for tumor targeting (Lee and Huang, 1996;Cho et al, 2005). Although receptor-mediated endocytosis is a promising approach for drug tar-UPTAKE PATHWAYS IN NONVIRAL GENE DELIVERY geting, most of the currently used ligands are internalized by clathrin-mediated endocytosis, and the poor intracellular trafficking associated with this significantly limits the transfection activities of the systems.…”
mentioning
confidence: 99%
“…16 Our previous results showed that the improvement of surface properties after introduction of F-PEG onto the baculovirus enhanced the transduction efficiency, indicating that the surface characteristics of gene carriers are an important parameter for efficient gene delivery. KB cells, which are broadly used as FR-positive cells, overexpressed the FRs on their membranes, 27,28 and were used in transduction experiments and competition assay for confirming the receptormediated delivery of F-P-Bac. These results indicated that attachment of folate as a tumor-targeting ligand made F-P-Bac a tumor-specific gene carrier.…”
Section: Discussionmentioning
confidence: 99%
“…However, their applications are seriously hampered by safety issues (i.e. the possibility of inducing severe immune responses, and the provocation of mutagenesis) [5][6][7], difficulty in their mass production and limitation in gene loading capacity [5]. In the last decade, synthetic nonviral vectors have been rapidly developed because of the advancement in polymer science and nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…These non-viral vectors are considered as alternatives to overcome the adverse effects of viral vectors. Among the various types of non-viral vectors, cationic polymers such as polylysine (PLL) [6,7], polyethylenimine (PEI) [8][9][10][11], polyamidoamine dendrimer (PAMAM) [12][13][14][15] and chitosan [16][17][18] have received a great deal of attention owing to their advantageous properties as compared with the viral and cationic liposome-based vectors. For examples, they are easy to prepare and to be chemically modified.…”
Section: Introductionmentioning
confidence: 99%